NMR-based leaf metabolic profiling of V. planifolia and three endemic Vanilla species from the Peruvian Amazon - Leyva, V.E.; Lopez, J.M.; Zevallos-Ventura, A.; Cabrera, R.; Cañari-Chumpitaz, C.; Toubiana, D.; Maruenda, H. (Elsevier, 2021)
The fruit of Vanilla planifolia is broadly preferred by the agroindustry and gourmet markets due to its refined flavor and aroma. Peruvian Vanilla has been proposed as a possible source for genetic improvement of existing Vanilla cultivars, but, little has been done to facilitate comprehensive studies of these and other Vanilla. Here, a nuclear magnetic resonance (NMR) metabolomic platform was developed to profile for the first time the leaves – organ known to accumulate vanillin putative precursors – of V. planifolia and those of Peruvian V. pompona, V. palmarum, and V. ribeiroi, with the aim to determine metabolic differences among them. Analysis of the NMR spectra allowed the identification of thirty-six metabolites, twenty-five of which were quantified. One-way ANOVA and post-hoc Tukey test revealed that these metabolites changed significantly among species, whilst multivariate-analyses allowed the identification of malic and homocitric acids, together with two vanillin precursors, as relevant metabolic markers for species differentiation.
Keywords: Metabolic profiling; https://purl.org/pe-repo/ocde/ford#1.06.03